DETERMINATION OF PRINCIPAL POSSIBILITY OF ALUMINA-THERMAL PROCESSING OF NON-UTILIZABLE SLAGS OF COPPER-SMELTING PRODUCTION - V. Ju. Stetsenko (Литьë и металлургия, 2011)
The principle technological possibility of aluminothermic processing of waste slag of copper-smelting production is determined.